Analysis of Embodied Energy in the Construction of The Prototype of Rammed Earth Wall - Suprahman, Faiz Hamdi; Nurafifah, Nisrina (Departement of Architecture, Universitas Islam Indonesia, 2022)
The construction sector has become the main target for reducing carbon emissions and world energy consumption in this decade. Reducing the energy consumption of buildings is an effective strategy for reducing carbon emissions. To achieve this kind of condition, the selection of building materials is an important factor, so the attempt to examine alternative building materials needsto be made. One of the attempts is by maximizing the potential of soil as a raw material. The technology of rammed earth wall has existed for centuries and now it is considered a sustainable material, but it has not yet become a popular discourse of alternative building material in Indonesia. This research aims to analyze embodied energy in rammed earth applications. This preliminaryresearch was conducted using the LCA inventory data method that was achieved by making a partial prototype of the rammed earth wall. This research resulted in several recommendations for rammed earth wall applications to reduce carbon emissions during the construction process. Keywords: Alternative Material; Energy Analysis; Rammed Earth Wall; Sustainable Material